Penerapan Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Pemecahan Masalah Siswa Pada Mata Pelajaran Ekonomi - Sopi Nursopiani; Astri Srigustini; Ati Sadiah (Pusat Riset dan Inovasi Nasional, 2026)
The problem addressed in this study was the low level of students’ problem-solving ability. This study aimed to improve students’ problem-solving ability in Economics through the implementation of the Problem Based Learning (PBL) model in Grade X-E of SMA Negeri 7 Tasikmalaya. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population consisted of all Grade X-E students of SMA Negeri 7 Tasikmalaya in the 2025/2026 academic year. The sample comprised Class X-E7 as the experimental group and Class X-E11 as the control group, selected through purposive sampling. The results revealed an improvement in students’ problem-solving ability in both groups. The Independent Samples t-Test showed a significance value of 0.014 (< 0.05), indicating a significant difference in problem-solving ability between the experimental and control groups. The N-Gain score of the experimental group was 0.71, categorized as high, while the control group obtained a score of 0.66, categorized as moderate. Furthermore, the effect size value of 0.47 indicated a moderate effect. Therefore, the Problem Based Learning (PBL) model was found to be more effective than conventional learning in improving students’ problem-solving ability in Economics.